An unusual case of abdominal mycobacterial infection: Case report and literature review - Pieter Ekermans; Rene de Gama; Celeste Kock; Ebrahim Hoosien; Tomas Slavik; Terry Marshall; Craig Corcoran; Jakko van Ingen (AOSIS, 2019)
This article presents a case of an HIV-infected paediatric patient with an unusual Mycobacterium genavense infection with predominantly abdominal organ involvement.